The Impact of the Global Financial Crisis on Investments in the Electric Power Sector : The Experience of India, Pakistan, and Bangladesh - Final Report - World Bank (World Bank, 2012)
The three large South Asian countries (India, Pakistan, and Bangladesh), which are the focus of this report, have drawn up large power capacity addition plans to provide for the rapidly increasing electricity demand in the region. The global financial crisis (the crisis), which became acute from September 2008 with the collapse of Lehman Brothers, has had a widespread impact across the world and across sectors through inducing recessionary conditions including falling demand, freezing financial markets, and loss of confidence. The purpose of this report is to assess whether the ambitious plans of these countries were adversely affected by the global financial crisis, and where relevant, to be able to plan better for such future shocks. The report is structured as follows: it starts with the executive summary. After this introductory chapter (chapter one), there are detailed country chapters (chapter two to four) which, inter-alia, map the different sources of financing available to the power sectors in the three target countries and discuss how these sources were affected by the crisis (if at all). An important aspect of this assessment has been the attempt to ring-fence the impact of the crisis per se on power sector projects, as distinct from other policy, implementation, and institutional capacity constraints that already exist.